Psychological and Cultural Factors Shaping Attitudes Toward Genetic Counselling Among Women with Breast Cancer: A Qualitative Study - Ayeni, Bolatito Funmilayo; Adejumo , Adebayo; Fagbenro, Dare Azeez; Omisola-Adebisi, Taiye Esther (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
Genetic counselling is very important for the prevention of cancer, early detection, and control. Despite its importance, little is known about the Psychological and Cultural Factors shaping attitude of patients toward genetic counselling as part of their treatment. To explore psychological and cultural factors that influence attitude of patients with breast cancer to genetic counselling in Lagos State University Teaching Hospital (LASUTH). The study utilized a qualitative method where data was collected through focus group discussion (FGD) with 8 participants, key informant interview (KII) with 7 participants, and in-depth interview (IDI) with 2 participants. The study found that psychological and cultural factors such as denial, belief in curse/punishment, unawareness, spiritual attack, belief in immunity to cancer, and low socio-economic status affect access to counselling and genetic testing. The result showed that an individual’s psychological and cultural beliefs play a significant role in shaping favourable attitude toward genetic counselling among breast cancer patients. Conquering psychological factors, spiritual beliefs and economic constraints will be central to improving patient belief and attitude towards genetic counselling.